Exceptional Aromatic Distribution in the Conversion of Palm-Oil to Biohydrocarbon Using Zeolite-Based Catalyst - I Gusti B. N. Makertihartha; Grandprix Thomryes Mart Kadja; Melia L. Gunawan; Rino R. Mukti; Subagjo Subagjo (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
A series of four catalysts, i.e. ZSM-5 (Si/Al = 25) (Z1), a combination of ZSM-5 (Si/Al = 25) and zeolite Y (Si/Al = 25) (Z2), zeolite Y (Si/Al = 25) (Z3), and ZSM-5 (Si/Al = 80) (Z4), was successfully prepared for catalytic cracking of palm oil. All three catalysts utilized silica as a binder without other additional components. Catalytic cracking tests showed that the aromatic distribution was very high, according to the following order: Z4 (98%) > Z1 (90%) > Z2 (84%) > Z3 (60%). It was shown that ZSM-5 promotes the formation of aromatics better than zeolite Y does. From 98% of aromatics products in Z1, 71% were benzene, toluene, and xylene (BTX). It appears that the formation of aromatics needs milder acidity since a higher number of acids extends the cracking reaction, resulting in the formation of more gaseous and heavy aromatics products. The results of this study show potential for the sustainable production of bio-hydrocarbons with exceptional aromatic distributions, which may fulfill the demands of the petroleum, petrochemical, and fine chemical sectors.